Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 3 - Equations and Problem Solving - Chapter 3 Test - Page 139: 6



Work Step by Step

We first use the distributive property to simplify. Then, using the properties of equality, we obtain that the value of the variable that satisfies the given equation, $ 9(x+4)=6(x-3) ,$ is \begin{array}{l}\require{cancel} 9x+36=6x-18 \\\\ 9x-6x=-18-36 \\\\ 3x=-54 \\\\ x=-\dfrac{54}{3} \\\\ x=-18 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.